Sex differences in helping effort reveal the effect of future reproduction on cooperative behaviour in birds - Downing, P; Griffin, A; Cornwallis, C (Royal Society, 2018)
The evolution of helping behaviour in species that breed cooperatively in family groups is typically attributed to kin selection alone. However, in many species, helpers go on to inherit breeding positions in their natal groups, but the extent to which this contributes to selection for helping is unclear as the future reproductive success of helpers is often unknown. To quantify the role of future reproduction in the evolution of helping, we compared the helping effort of female and male retained offspring across cooperative birds. The kin selected benefits of helping are equivalent between female and male helpers—they are equally related to the younger siblings they help raise—but the future reproductive benefits of helping differ because of sex differences in the likelihood of breeding in the natal group. We found that the sex which is more likely to breed in its natal group invests more in helping, suggesting that in addition to kin selection, helping in family groups is shaped by future reproduction.